Therapeutic strategies for afatinib‐resistant lung cancer harboring HER2 alterations. Issue 5 (15th April 2018) - Torigoe, Hidejiro; Shien, Kazuhiko; Takeda, Tatsuaki; Yoshioka, Takahiro; Namba, Kei; Sato, Hiroki; Suzawa, Ken; Yamamoto, Hiromasa; Soh, Junichi; Sakaguchi, Masakiyo; Tomida, Shuta; Tsukuda, Kazunori; et al.
Abstract : Human epidermal growth factor receptor 2 (HER2) plays an important role in the pathogenesis of various cancers. HER2 alterations have been suggested to be a therapeutic target in non‐small‐cell lung cancer (NSCLC), just as in breast and gastric cancers. We previously reported that the pan‐HER inhibitor afatinib could be a useful therapeutic agent as HER2‐targeted therapy for patients with NSCLC harboring HER2 alterations. However, acquired resistance to afatinib was observed in the clinical setting, similar to the case for other HER inhibitors. Thus, elucidation of the mechanisms underlying the development of acquired drug resistance and exploring means to overcome acquired drug resistance are important issues in the treatment of NSCLC. In this study, we experimentally established afatinib‐resistant cell lines from NSCLC cell lines harboring HER2 alterations, and investigated the mechanisms underlying the acquisition of drug resistance. The established cell lines showed several unique afatinib‐resistance mechanisms, including MET amplification, loss of HER2 amplification and gene expression, epithelial‐to‐mesenchymal transition (EMT) and acquisition of cancer stem cell (CSC)‐like features. The afatinib‐resistant cell lines showing MET amplification were sensitive to the combination of afatinib plus crizotinib (a MET inhibitor), both in vitro and in vivo. The resistant cell lines which showed EMT or had acquired CSC‐like features remained sensitive to docetaxel, like the parental cells. These findings may provide clues to countering the resistance to afatinib in NSCLC patients with HER2 alterations. Abstract : This is the first report in which afatinib‐resistant cell lines were experimentally established using HER2‐altered NSCLC cell lines, and their resistance mechanisms were thoroughly investigated. As a result, the afatinib‐resistant NSCLC cell lines displayed various resistant mechanisms such as MET amplification, loss of HER2 amplification, and epithelial to mesenchymal transition or cancer stem cell‐like features, with specific sensitivity to various drugs such as MET‐tyrosine kinase inhibitor crizotinib.